Genotyping, serotyping and determination of mating-type of Cryptococcus neoformans clinical isolates from São Paulo State, Brazil - Matsumoto, Marcelo Teruyuki [UNESP]; Fusco-Almeida, Ana Marisa [UNESP]; Baeza, Lilian Cristiane [UNESP]; Melhem, Márcia de Souza Carvalho; Medes-Giannini, Maria José Soares [UNESP] (Instituto de Medicina Tropical, 2007)
Cryptococcus neoformans, pertencente à classe dos basidiomicetos, é um importante patógeno, principalmente em pacientes imunocomprometidos. Neste estudo, 47 isolados clínicos de C. neoformans de várias regiões do Estado de São Paulo foram avaliados quanto aos sorotipos e ao mating-type por PCR. A diversidade genética foi analisada por PCR-fingerprinting com a seqüência iniciadora específica para regiões microssatélite (GACA)4, RAPD com o iniciador 6 (Amersham Pharmacia Biotech) e por RFLP do gene PLB1 digerido com AvaI. Todos os isolados foram obtidos de pacientes HIV positivos e identificados como sorotipo A e MATalfa. A maioria dos isolados pertencia ao tipo molecular VNI (45/47) e apenas dois foram VNII quando analisados por PCR-fingerprinting e PCR-RFLP. Homogeneidade alta foi obtida com o iniciador (GACA)4, com a maioria dos isolados apresentando correlação alta (> 0.9). Os resultados do RAPD, por sua vez, revelaram maior heterogeneidade com número maior de perfis moleculares. Por PCR-RFLP, nenhum tipo molecular novo foi encontrado, realçando a idéia de que em genes conservados como PLB1, as diferenças podem ser resultantes de divergências evolutivas dentro do complexo C. neoformans, separando os isolados nos oito subtipos moleculares já estabelecidos. Nossos resultados fornecem novas informações sobre a epidemiologia molecular de C. neoformans na região sudeste do Brasil.

The basidiomycetous yeast Cryptococcus neoformans is an important fungal pathogen mainly in immunocompromised patients. In this study, 47 clinical isolates of C. neoformans from regions of São Paulo State were studied serologically by using the Crypto Check Iatron RM 304-K kit, their genetic diversity was estimated by PCR-fingerprinting with a microsatellite-specific sequence (GACA)4, RAPD with primer 6 (Amersham Pharmacia Biotech), PCR-restriction fragment length polymorphism (RFLP) analysis of the phospholipase B gene (PLB1) digested with AvaI and mating type analysis by PCR. All 47 strains isolated from HIV positive patients included in this study were serotype A and MATalpha. The majority of the isolates (45/47) were VNI and only two were VNII by PCR-fingerprinting and PCR-RFLP analysis. High degree of homogeneity was observed when (GACA)4 was used, being highly correlated (> 0.9). In contrast, the RAPD analysis was more heterogeneous with higher number of molecular profiles. By PCR-RFLP, no new molecular type was found, enhancing the suggestion that the differences based on conserved gene as PLB1, can be resultant of ongoing divergent evolution within the C. neoformans complex, into the current eight subtypes. Our results furnish new information on the molecular epidemiology of C. neoformans in the southeast region of Brazil.
Genotipagem, sorotipagem e determinação de mating-type de isolados clínicos de Cryptococcus neoformans do Estado de São Paulo, Brasil
Keywords: Cryptococcus; Epidemiology; Mating type; RAPD; PCR fingerprinting; RFLP